Serum Ferritin and Non-alcoholic Fatty Liver Disease: A Meta-analysis and Systematic Review - Yan, Junxin; Guan, Tongjuan; Guo, Meiqi; Liu, Jingfang (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Previous studies have shown that hyperferritinemia is a common phenomenon in non-alcoholic fatty liver dis- ease patients. We aim to further explore the relationship between serum ferritin levels and non-alcoholic fatty liver disease using a meta-analysis. Materials and Methods: Four Library databases were electronically searched from inception until December 2021 to find prospective cohort or case–control studies examining the relationship between serum ferritin levels and non-alcoholic fatty liver disease, and all kinds of literature were screened according to the inclusion and exclusion criteria. The odds ratio and other related data were extracted, and a meta-analysis was performed. Results: Eleven studies examining the relationship between serum ferritin levels and non-alcoholic fatty liver disease were included. The serum ferritin levels in the non-alcoholic fatty liver disease group were significantly higher than those without non-alcoholic fatty liver disease group (1.54 ng/mL, 95% CI: 0.85-2.23, P < .001). Serum ferritin levels were significantly associated with the risk of non-alcoholic fatty liver disease in both men and women (odds ratio = 2.36, 95% CI: 1.41-3.93, P = .001 and odds ratio = 2.93, 95% CI: 1.83-4.69, P < .001, respectively), and after adjusting for the parameters, the relationships were still shown to be significant in men and women (odds ratio = 2.24, 95% CI: 1.64-3.05, P < .001 and odds ratio = 3.30, 95% CI: 2.13-5.11, P < .001, respectively). Conclusion: Serum ferritin levels were higher in patients with non-alcoholic fatty liver disease than in those without non-alcoholic fatty liver disease and were associated with the risk of non-alcoholic fatty liver disease in both men and women.